Interpretatio Islamica and the Unraveling of the Ancient Sabian Mysteries - Hines, Maurice (AUC Knowledge Fountain, 2023)
This thesis makes some bold claims about the identity of the Qur’anic Sabians (Ṣābi’ūn) and their symbiotic relationship with various Near Eastern religions including Judaism, Christianity, and Islam. Thrice mentioned in the Qur’an, they clung to an ancient religion - or perhaps the most ancient – that spanned the entire Eastern hemisphere and provided not only the structural foundations of human civilizations, but also their religious, philosophical, and intellectual foundations. However, their creed had undergone a variety of changes over time including a shift in the conception of God from a personal to a transcendent deity, the worship of angels, celestial bodies, and idols as intercessors between God and man, a reconceptualization of prophethood, and the preference of some prophets and rejection of others. In turn, various prophets, sages, and reformers strove to correct these beliefs and turn people back to the original religion. This was the mission of the three prominent Abrahamic traditions, but Sabianism persisted as their strongest antagonist. These claims are supported by early classical Arabic texts, a cadre of interdisciplinary scholars across regions, as well as a variety of contemporary non-academic esoterists. While the grain of contemporary scholarship, represented by the likes of D. Chwolsohn, Sarah Stroumsa, François de Blois, Kevin van Bladel, and Khazʿal al-Mājidī, has been to disconnect those sects of the Ḥarrānians in Asia Minor and the Mandaeans of Iraq who have historically been called Sabians from those intended in the Qur’an, I offer a different solution to understanding their identity. In this thesis, I revisit a selection of the oft-cited primary Arabic texts like al-Ṭabarī and other exegetical works, Ibn al-Nadīm’s al-Fihrist, al-Andalusī’s Ṭabaqāt al-Umam, and al-Shahrastānī’s Al-Milal wa al-Niḥal to make novel revelations about the purpose of these texts with regards to Sabianism. These works will be examined within the framework of interpretatio, an ancient civilizational phenomenon in which one civilization integrates its religion, culture, and practices into another for purposes of enrichment, reform, and coexistence. I will show how Muslim scholars and Sabians employed the concept of interpretatio islamica. According to these texts, I will argue that not only were the Ḥarrānians and the Mandaeans considered Sabians, but some scholars believed that the ancient Egyptians and Pre-Islamic Arabs also represented iterations of Sabianism, a perspective worthy of investigation. Based on these perspectives, I will demonstrate how the Qur’an engages Sabian beliefs about prophets Noah, Abraham, Moses, Jesus, and Mary polemically. This will allow us to conclude that the Qur’an was performing interpretatio islamica vis-a-vis the Sabians from the beginning and is thus a viable framework to discuss other religions in Arabic texts.